The influence of carbon nanotube coated-carbon fibers on thermal residual stresses of Multi-Scale hybrid composites: Analytical approach. (15th December 2021) - Malekimoghadam, Reza; Icardi, Ugo; Hosseini, Seyyed Ahmad
Abstract: The effect of carbon nanotube (CNT) coated-carbon fibers on thermal residual stresses of multi-scale hybrid composites is assessed employing analytical approach. The model comprises carbon fiber, coating region and surrounding matrix, in which the coating region around core fiber encompasses CNTs and matrix. Considering three configurations of grown CNTs on the fiber surface including axially, radially and randomly oriented, the mechanical properties of various coating regions are acquired employing the Eshelby–Mori–Tanaka method in conjunction with an equivalent continuum approach. Utilizing the total energy minimization method, the closed-form solution of the thermal residual stresses of hybrid composite is obtained. The results disclose a noteworthy influence of CNT–coating on the reduction of interfacial stresses which precludes debonding at interface and attenuates the effect of thermal expansions mismatch between the carbon fiber and matrix. Furthermore, the results demonstrate that unlike radially oriented CNTs, the existence of axially and randomly oriented CNTs at the coating region has a remarkable diminishing effect on residual interfacial stresses. It is also shown that increasing the coating thickness leads to reduction of maximum interfacial stresses even at a constant CNT volume fraction. A close agreement exists between predicted outcomes by the proposed analytical approach and published data in the literature.